1980
DOI: 10.1007/bf00337040
|View full text |Cite
|
Sign up to set email alerts
|

Two coupled oscillators as a model for the coordinated finger tapping by both hands

Abstract: Recently, it was found that rhythmic movements (e.g. locomotion, swimmeret beating) are controlled by mutually coupled endogeneous neural oscillators (Kennedy and Davis, 1977; Pearson and Iles, 1973; Stein, 1974; Shik and Orlovsky, 1976; Grillner and Zangger, 1979). Meanwhile, it has been found out that the phase resetting experiment is useful to investigate the interaction of neural oscillators (Perkel et al., 1963; Stein, 1974). In the preceding paper (Yamanishi et al., 1979), we studied the functional inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
176
2
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(199 citation statements)
references
References 11 publications
10
176
2
2
Order By: Relevance
“…These two patterns of coordination are generically found in rhythmic limb movement (Kelso, 1984). Without practice, other, intermediate phase relationships are more variable and biased toward these two basic patterns (Yamanishi et al, 1980). That the stability of patterns of relative timing is not only a sufficient, but also a necessary condition for coordination is underlined by the observation that a loss of coordination is accompanied by a loss of stability (Schöner & Kelso, 1988a).…”
Section: Coordination In Limb Movementsmentioning
confidence: 99%
“…These two patterns of coordination are generically found in rhythmic limb movement (Kelso, 1984). Without practice, other, intermediate phase relationships are more variable and biased toward these two basic patterns (Yamanishi et al, 1980). That the stability of patterns of relative timing is not only a sufficient, but also a necessary condition for coordination is underlined by the observation that a loss of coordination is accompanied by a loss of stability (Schöner & Kelso, 1988a).…”
Section: Coordination In Limb Movementsmentioning
confidence: 99%
“…These subdivisions create a salient short-long or long-short timing pattern. This analysis leads us to consider the possibility that in performing the Yamanishi et al (1980) task, the participants controlled the coordination between the hands by complying with the timing constraints inherent to the production of groups of rhythmic taps. We refer to this hypothesis as the timing control hypothesis.…”
Section: Timing Control Hypothesismentioning
confidence: 99%
“…From this perspective, we want to show that the phasing between the hands may depend, at least in part, on the participant's capacity to generate the required timing patterns. To this end, we first analyze the timing requirements of the bimanual finger-tapping task used by Yamanishi et al (1980). Our analysis of the Yamanishi et al task leads us to the expectation that the main results observed in the bimanual condition should be reproducible in a single-hand tapping task involving similar timing requirements.…”
mentioning
confidence: 99%
See 2 more Smart Citations